Monitoring and Evaluating Agricultural Water Management Projects : Better Tools for Better Results - World Bank (Washington, DC, 2012)
Increasing agricultural production is necessary to feed growing populations, raise the incomes of poor farmers, and boost national export revenues. But in poor, water-scarce areas of the world, it is impossible to raise production without first finding ways to get more out of limited supplies of water, the ultimate scarce resource. Increasing the efficiency with which water is used is one of the chief goals of agricultural water management (AWM). Continual improvements in the efficiency of water use depend on close monitoring and careful evaluation. But despite the scale and scope of AWM projects around the world, and their criticality to global efforts to reduce rural poverty and increase food security, the monitoring and evaluation (M&E) of AWM projects need considerable improvement. The report stressed the need for greater emphasis on outcomes and impact measurement in project design. It also concluded that the effective implementation of projects was routinely compromised by inadequate supervision. M&E is strongest when there is a participatory quality to data collection and evaluation, so that stakeholders are invested in the project's successful implementation and aware of its successes and failures.